Strategic sophistication of adolescents: Evidence from experimental normal-form games - Simon Czermak; Francesco Feri; Daniela Rützler; Matthias Sutter (Institute for the Study of Labor (IZA), 2010)
We examine the strategic sophistication of adolescents, aged 10 to 17 years, in experimental normal-form games. Besides making choices, subjects have to state their first- and second-order beliefs. We find that choices are more often a best reply to beliefs if any player has a dominant strategy and equilibrium payoffs are not too unequal. Using a mixture model we can estimate for each subject the probability to be any of eight different strategic and non-strategic types. The econometric estimation reveals that older subjects are more likely to eliminate dominated strategies, and that subjects with good math grades are more strategic.
Keywords: C72; C91; 330; Strategic thinking; beliefs; experiment; age; adolescents; Jugendliche; Normalformspiel; Spieltheorie; Entscheidung; Gruppenentscheidung; Test; Schweden